Analysis of the phenomenon of keeping endangered animals as a trend - Ekawati, Kintan Nurani; Mukti, Yuliansari Adhi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Indonesia is a country with diverse fauna. However, many animals are experiencing an extinction crisis, one of the causes is the exploitation of these rare animals, one of which is for free keeping. Wild animals have natural instincts that evolved with their evolution and help them survive in their natural habitat. When wild animals are kept in different environments, such as captivity or shelters, they often lose or change some aspects of their original instincts. The protection of rare and endangered wildlife species is of international concern, as biodiversity conservation is essential for survival. Unfortunately, the enforcement of these protected wildlife regulations is not strict enough and there are still many violations, so it is important for the Indonesian government and its citizens to work together to ensure effective implementation of wildlife protection regulations. This research method uses a qualitative approach with data collection from literature studies and uses interpretation analysis techniques. The importance of wildlife conservation in Indonesia cannot be ignored. It is important for Indonesians to follow applicable regulations and participate in protected wildlife conservation efforts to maintain the country's biodiversity. This study illustrates the factors that lead to the keeping of wild and endangered animals and the role of the government in this regard and answers how the phenomenon has become a trend in high society.